1977
DOI: 10.1164/arrd.1977.116.4.685
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Lymphoepithelial Nodules in the Rat

Abstract: Using morphologic and ultrastructural criteria, the present study in the rat was undertaken to distinguish lymphoepithelial modules from lymphoid aggregates and lymph modes, and to demonstrate the uptake and transport of ferritin and latex particles, instilled in the trachea, by the lymphoepithelium. Unlike lymph nodes or lymphoid aggregates, lymphoepithelial nodules can be distinguished by the following characteristics of the lymphoepithelium: it is flattened and devoid of goblet cells; it contains intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The morphology of bronchus-asso ciated lymphoid tissue (BALT) has been studied in several animals [Bienenslock et al, 1973a;Bienenslock and Johnston, 1976] including the rat [Chamberlain et al, 1973;Vaiet al, 1976;Fournier et al, 1977;Gregson et al, 1979a;Plesch, 1982;Plesch et al, 1983]. The BALT consists of a net-work of reticulum cells in which lympho cytes and macrophages are situated.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of bronchus-asso ciated lymphoid tissue (BALT) has been studied in several animals [Bienenslock et al, 1973a;Bienenslock and Johnston, 1976] including the rat [Chamberlain et al, 1973;Vaiet al, 1976;Fournier et al, 1977;Gregson et al, 1979a;Plesch, 1982;Plesch et al, 1983]. The BALT consists of a net-work of reticulum cells in which lympho cytes and macrophages are situated.…”
Section: Introductionmentioning
confidence: 99%
“…The epithelium in the nasopharyngeal lymphoepithelial tissue, the so-called "lymphoepithelium (Jolly, 1914)", was heavily infiltrated with lymphoid cells and could not be established its deep border. This type of epithelium has been observed in the lymphoepithelial tissues from different anatomical sites, such as the pharyngeal tonsil (Leela and Kanagasuntheram, 1973), palatine tonsil (Fioretti, 1961;Kawaguchi, 1967;Takagi and Saito, 1974a, b;Saito, 1976), lingual tonsil (Nair and Rossinsky, 1984), bronchus-associated lymphoid tissue (Bienenstock and Johnston, 1976;Fournier et , al., 1977), Peyer's patches (Owen and Jones, 1974;Smith and Peacock, 1980) and appendix (Bockman et al, 1975), and Fioretti (1961) termed i as the "Lymphoepitheliale Symbiose".The lymphoepithelium is not regarded as a pathological state such as infection but as a physiological phenomenon in view of the constancy which it is observed (Takagi and Saito, 1974b;Fournier et al, 1977;Howie, 1981). It is suggested that the epithelial cells and the lymphoid cells coexist within the lymphoepithelium with maintaining any physiological relationships, and play an important role as the first level of the defense mechanism in the lymphoepithelial tissue.…”
Section: Discussionmentioning
confidence: 92%
“…One must assume that the differences lie in the degree of antigenic exposure and to interspecies or interstrain differences. Fournier, Vai, Devenne & Pariente (1977) tried to distinguish between lymphoepithelial nodules and lymphoid cell 'clusters', but the results presented above lead to the conclusion that these structures are merely dilTerent developmental stages of the same entity (BALT), and that subclassifications of BAL Tare perhaps unnecessary complications.…”
Section: Gregson Davey and Prentice Discussionmentioning
confidence: 99%